The church without the church : desert orthodoxy in Flannery O'Connor's Dear Old Dirty Southland - Shaddix, M. K. (Trinity College (Dublin, Ireland). School of English, 2011)
In the nearly fifty years since her death, the critical study of the life and work of Mary Flannery O'Connor has been conventionally delimited to two critical parameters: the greater "South" and the Church of Rome. My research challenges the longstanding conception of O'Connor as inherent to a monolithic South and to orthodox Roman Catholicism. My first chapter, "Monsters, Monoliths, and Middle Georgia: Flannery O'Connor and the 'Dear Old Dirty Southland,'" contextualizes O'Connor's work within the American scene by detailing the varied political and literary histories of the "North" and "South" as well as problematising the notion of region-specific aesthetics, notably American/Non-Southern realism and Southern Gothicism. My second chapter, "'One jesus [is] Just as Bad as Another': Orthodoxy as Ecumenical Blasphemy in the Fiction of Flannery O'Connor," contests the body of scholarship which attempts to explain O'Connor's work in terms of Roman orthodoxy.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.